KARAKTERISTIK SENSORI DAN FISIK KULIT PANGSIT GORENG DENGAN SUBSTITUSI TEPUNG YANG BERBEDA PADA PENYIMPANAN DINGIN DAN BEKU - Nuri Arum Anugrahati; Natania Natania; Andrew Andrew (JURNAL AGROTEKNOLOGI, 2017)
Wonton wrapper is a type of pasta that has a similar composition with noodle, such as wheat flour, water, egg, salt, and kansui. Indonesian people has also consumed wonton wrapper but it has been limited due to the difficulty of wheat flour supply as it’s main ingredient. To reduce the dependency of imported wheat flour, this experiment was held to determine tapioca, sago, and glutinous rice as a substitute to wheat flour. The aims of this research were to determine the type of flour to substitute wheat flour in fried wonton wrapper making, to determine the protein percentage of wheat flour in fried wonton wrapper making, and to determine the sensory and physical characteristics of wonton wrapper on cold and frozen storage. This research was conducted by RAL (completely randomized design) using two treatment factors are three kinds of flour (tapioca, sago, and glutinous rice) and three substitution level of concentration (15, 30, and 45%). The organoleptic result showed that fried wonton wrapper made from medium protein wheat flour with 30% tapioca flour substitution was the best treatment to produce a good quality since it had a higher crunchiness, acceptance, and substitution level. Sensory and physical characteristics of wonton wrapper has been maintained during 4 weeks of freezing storage. Keywords: fried wonton wrapper, wheat flour, tapioca